2005
DOI: 10.1002/mus.20312
|View full text |Cite
|
Sign up to set email alerts
|

Spinal and cranial hypertrophic neuropathy in multiple sclerosis

Abstract: Two patients with multiple sclerosis developed symptomatic chronic inflammatory demyelinating polyneuropathy with massive spinal or cranial nerve hypertrophy revealed by neuroimaging. Sural nerve biopsy in one showed only moderate demyelination, axonal loss, and onion-bulb formation, illustrating dichotomy between severe proximal and milder distal nerve involvement. Patients with coexistent central and peripheral demyelination usually are symptomatic from dysfunction at one site or the other, but not from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Patients with Behcet's disease may have axonal polyneuropathy, more prominent in the lower extremities (Birol et al 2004;Yazıcı et al 2001), while MS patients may also show signs of peripheral nervous system involvement, often as demyelination (Couratier et al 2004;Quan et al 2005). Our results were similar to the literature, but the frequency of abnormal electrophysiological findings in our study was very low.…”
Section: Discussionsupporting
confidence: 87%
“…Patients with Behcet's disease may have axonal polyneuropathy, more prominent in the lower extremities (Birol et al 2004;Yazıcı et al 2001), while MS patients may also show signs of peripheral nervous system involvement, often as demyelination (Couratier et al 2004;Quan et al 2005). Our results were similar to the literature, but the frequency of abnormal electrophysiological findings in our study was very low.…”
Section: Discussionsupporting
confidence: 87%
“…Previous reports of definite MS with definite CIDP are presented in Table 5. 6,7,[9][10][11][14][15][16][17] Electrophysiological studies in our patients revealed evidence of greater involvement of nerve roots and proximal segments of peripheral and cranial nerves than the distal components, consistent with the pathology of the disease. 19,32,34 Partial conduction block or temporal dispersion of action potentials occurred in at least one of the tested nerves in all 5 of our patients, whereas only 4 of all 18 previously reported cases did (22.2%, P = 0.008).…”
Section: Discussionmentioning
confidence: 78%
“…However, these findings were accompanied by a loss of spasticity and a persistence of extensor plantar responses. 6,7,9,11,14,17 Increased CSF protein documented in our patients is more typical in polyneuropathy, including CIDP. Previous reports of definite MS with definite CIDP are presented in Table 5.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations